Etude bibliographique et analyse economique de l'effet des phosphates naturels sur certaines plantes cultivees de l'Afrique de l'Est - Seyoum, E.; McIntire, John M. (1987)
Assesses the performance of phosphate rock compared to other phosphates on cereals and feed crops, and the conditions under which it raises yield. Anayses its profitability.